Effect of male aggressivity profile on female chemical choice in Nile tilapia - Rossi, V. S. [UNESP]; de Sá, M. Borges [UNESP]; Sugihara, V. S. [UNESP]; de Mello, I. M. [UNESP]; Giaquinto, P. C. [UNESP] (Springer Nature, 2019)
Selection favors females that make use of reliable information on the genetic quality of males, which affects mating decisions. Although studies have shown that females prefer dominant males, it may not be adaptive for females to choose very aggressive males, as aggression can be misdirected towards females. The Nile tilapia Oreochromis niloticus is an appropriate model species for testing this dilemma because it shows dominance hierarchy, in which dominant males defend territories, build nests, court females and have priority of access to mating. In addition, in this species, odor recognition affects sexual and social status. We tested whether females can select, by means of chemical cues, dominant males with aggressive profiles. Females were allowed to choose between the odors of two dominant males differing in their aggression level. Our findings show that females discriminate dominant males that have a high aggressivity profile in favor of males that are less aggressive.
Keywords: Aggression; Chemical cues; Dominance; Fish; Mate choice; Sexual selection